Micropore‐Forming Gelatin Methacryloyl (GelMA) Bioink Toolbox 2.0: Designable Tunability and Adaptability for 3D Bioprinting Applications - Yi, Sili; Liu, Qiong; Luo, Zeyu; He, Jacqueline Jialu; Ma, Hui‐Lin; Li, Wanlu; Wang, Di; Zhou, Cuiping; Garciamendez, Carlos Ezio; Hou, Linxi; Zhang, Jin; Zhang, Yu Shrike (Small (Weinheim an der Bergstrasse, Germany), 2022)
It is well‐known that tissue engineering scaffolds that feature highly interconnected and size‐adjustable micropores are oftentimes desired to promote cellular viability, motility, and functions. Unfortunately, the ability of precise control over the microporous structures within bioinks in a cytocompatible manner for applications in 3D bioprinting is generally lacking, until a method of micropore‐forming bioink based on gelatin methacryloyl (GelMA) was reported recently. This bioink took advantage of the unique aqueous two‐phase emulsion (ATPE) system, where poly(ethylene oxide) (PEO) droplets are utilized as the porogen. Considering the limitations associated with this very initial demonstration, this article has furthered the understanding of the micropore‐forming GelMA bioinks by conducting a systematic investigation into the additional GelMA types (porcine and fish, different methacryloyl‐modification degrees) and porogen types (PEO, poly(vinyl alcohol), and dextran), as well as the effects of the porogen concentrations and molecular weights on the properties of the GelMA‐based ATPE bioink system. This article exemplifies not only the significantly wider range of micropore sizes achievable and better emulsion stability, but also the improved suitability for both extrusion and digital light processing bioprinting with favorable cellular responses. A micropore‐forming gelatin methacryloyl (GelMA) aqueous two‐phase bioink toolbox 2.0 is reported with a systematic investigation into a variety of GelMA types and porogen types. This article exemplifies not only the significantly wider range of micropore sizes achievable and better emulsion stability than the initial version, but also the improved suitability for various bioprinting modalities featuring favorable cellular responses.